Circulating DNA methylation-based diagnostic, prognostic, and predictive biomarkers in colorectal cancer - Beibei Chen; Huan Zhao; Huihui Hu; Haili Shang; Hui Wang; Zhentao Yao; Jinxi Huang; Huifang Lv; Weifeng Xu; Jianzheng Wang; Caiyun Nie; Jing Zhao; et al. (Scientific Reports)
Abstract Plasma DNA methylation SEPTIN9, Syndecan 2 (SDC2), and Branched Chain Amino Acid Transaminase 1 (BCAT1) tests have served as valuable diagnostic, prognostic, and predictive markers for colorectal cancer (CRC). In this study, we analyzed data including 104 eligible CRC patients, 138 colorectal benign diseases, and 106 healthy subjects in our hospital from January 2019 to May 2023. This study was approved by the Medical Ethics Committee of Henan Cancer Hospital (Approval No.2018156). A real-time polymerase chain reaction-based gene panel was used to detect the methylation of SEPTIN9, SDC2, and BCAT1. The composite score (P) was calculated according to the cycle threshold (Ct) values of the three methylated genes using the logistic regression equation. The consistency of assay and pathological diagnosis were evaluated with kappa analyzed by IBM SPSS Statistics. The median survival time was obtained by Kaplan-Meier survival analysis. Statistical figures were all carried out using Origin software. The three genes were found to be significantly methylated in ctDNA of CRC patients compared to patients with colorectal benign diseases and healthy controls. The sensitivity was 86.1%, the specificity was 97.6%, and the area under the curve of 0.929. Positive predictive value (PPV) was 57.2%, and Negative predictive value (NPV) was 99.5%. No statistically significant differences in diagnostic efficiency were observed in relation to different types of stages. Moreover, there was a significant difference in the expression of composite scores between survival periods greater than 1 year and less than 1 year (p < 0.01). The composite score (P) derived from the ctDNA methylation levels of SEPTIN9, SDC2, and BCAT1 can be used for CRC diagnosis with high sensitivity and specificity. A combination of ctDNA methylation was proved to be an effective diagnostic, prognostic, and predictive biomarker in colorectal cancer.